Sistema LMS y su influencia en el contexto educativo inclusivo en los estudiantes de la carrera de Pedagogía de las Ciencias Experimentales Informática, de la Universidad Técnica de Babahoyo, periodo diciembre 2022 - abril 2023 - Rizzo Loor, Sonia Eloisa (2023)
The research focuses on the impact of Learning Management Systems (LMS) on inclusive education in the Pedagogy of Experimental Sciences and Computer Science program at the Technical University of Babahoyo. The study used a descriptive and quantitative methodology, surveying 114 students to determine how LMSs influence the quality of educational activities and the students' learning experience. The results indicate that LMSs can enhance the educational inclusion of students with disabilities, although more research is needed to identify specific adaptations that can meet their needs. A crucial point in the research is that LMS systems have potential benefits for students by enabling enhanced educational activities. These benefits may include greater efficiency in learning, greater accessibility, and greater inclusion of students with disabilities. In addition, it is recommended to promote education on the effective use of LMSs among students to encourage greater participation and engagement in their use and to overcome barriers to their effective implementation. Overall, the research highlights the importance of LMS in the inclusive educational context and suggests the need to continue exploring their impact on student learning, also as a last point is that it should continue to invest in the improvement and development of LMS systems within the University, which promotes the use of these applications thus benefiting student inclusion.